2014
DOI: 10.1007/s10726-014-9418-2
|View full text |Cite
|
Sign up to set email alerts
|

A Group Decision-Making Aggregation Model for Contractor Selection in Large Scale Construction Projects Based on Two-Stage Partial Least Squares (PLS) Path Modeling

Abstract: Modern projects are normally characterized by huge investments, long construction periods, and complex technology. Therefore, the selection of an appropriate contractor for smooth project delivery is challenging. Previous studies attempted to develop suitable frameworks for contractor selection. However, correlation among indicators, the subjectivity of indicator weights, and heterogeneity among experts' professional capabilities for selecting contractors were not successfully removed from the decision-making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 72 publications
(106 reference statements)
0
27
0
Order By: Relevance
“…Table 1 shows the most commonly cited criteria dealing with "Contractor selection criteria" or "Contractor pre-qualification criteria". Furthermore, the researchers suggested other criteria, such as risk [19], environment [20,34], equipment resources and current workload [19,21,22,37,38], company characteristics [2] and business ethics [10], legal capacity [7,10,15], warranty [1,10], design [15,18], and firm background innovative capabilities [23].…”
Section: Criteria Consideredmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the most commonly cited criteria dealing with "Contractor selection criteria" or "Contractor pre-qualification criteria". Furthermore, the researchers suggested other criteria, such as risk [19], environment [20,34], equipment resources and current workload [19,21,22,37,38], company characteristics [2] and business ethics [10], legal capacity [7,10,15], warranty [1,10], design [15,18], and firm background innovative capabilities [23].…”
Section: Criteria Consideredmentioning
confidence: 99%
“…This method involves new forms of supplying priority information. Liu et al [20] suggested a Group Decision-Making aggregation approach based on Two-Stage Partial Least Squares (PLS) Path Modeling. Attar et al [21] presented the contractor prequalification model by Support Vector Machines approach.…”
Section: Introductionmentioning
confidence: 99%
“…However, correlation among attributes, subjectivity of attributes weights, and heterogeneity among experts' professional capabilities for selecting contractors could not be successfully removed from the decision-making process [43]. Consequently, it is suggested that the problem be presented as GDMM and appropriate methods for evaluating and selecting contractors should also be applied.…”
Section: Problem Formulationmentioning
confidence: 99%
“…To address such issue, Liu et al (2014), Liu et al (2015b), Liu, Huo, Liao, Gong, and Xue (2015a), Liu, Huo, Liang, Sun, and Hu (2016), Liu et al (2017) have conducted a series of empirical studies to identify key factor affecting PDSs selection (i.e. owners' characteristics factors, contractors' characteristics factors, and projects' characteristics factors).…”
Section: Introductionmentioning
confidence: 99%